PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL MEDIASI - Yunovirul, Dwi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of the study was to analyze the effect of price and product quality on purchasing decisions with buying interest as a mediation variable in Abiza Chicken restaurant. This study uses a quantitative approach with the type of causality research. The population used is the consumer of Abiza Chicken restaurant. Samples were taken as many as 95 respondents who have been determined by the Formula Slovin. Data collection method using questionnaires. Data Processing used is Partial Least Square (PLS) with SmartPLS software version 3 and Sobel test. The results showed that buying interest is proven to mediate the price and quality of the product to the purchase decision. For that, abiza chicken restaurant must improve its quality again to attract the attention of consumers to try and always buy the product.